2022
DOI: 10.1177/11206721221124684
|View full text |Cite
|
Sign up to set email alerts
|

Polyhexamethylene biguanide hydrochloride (PHMB)-properties and application of an antiseptic agent. A narrative review

Abstract: The prevention and management of ocular surface infections is still one of the great challenges for ophthalmologists. The spread of antimicrobial resistance makes it necessary to use antiseptic substances with a broad antimicrobial spectrum. Polyhexamethylene biguanide hydrochloride (Polyhexanide, PHMB) is a broad-spectrum antiseptic with excellent tolerance and a low-risk profile. Its physicochemical action on the phospholipid membrane and DNA replication or repair mechanism, prevents or impedes the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Furthermore, mouth rinses with active ingredients BNZ and PHMB caused a higher dental staining as compared to OCT and OCTP and lower staining than CHX in this study. The results of this study are also in good agreement with the literature, 11 where BNZ was found to cause lower light and dark shades on a provisional acrylic resin than after treatment with a CHX-containing mouth rinse. These agreements underline the applicability of the new model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, mouth rinses with active ingredients BNZ and PHMB caused a higher dental staining as compared to OCT and OCTP and lower staining than CHX in this study. The results of this study are also in good agreement with the literature, 11 where BNZ was found to cause lower light and dark shades on a provisional acrylic resin than after treatment with a CHX-containing mouth rinse. These agreements underline the applicability of the new model.…”
Section: Discussionsupporting
confidence: 91%
“… 10 Besides, benzydamine hydrochloride (BNZ), polyhexamethylene biguanide hydrochloride (PHMB), and hexetidine gluconate (HEX) are further alternative antibacterial agents in oral rinsing products. 11 12 While the staining potential of CHX-containing rinsing solutions has been investigated extensively in vitro , there is a lack of data from products containing OCT, OCTP, BNZ, PHMB, and HEX.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by our findings, we propose a new bonding strategy assisted by polyhexamethylene biguanide (PHMB) assembly that can crack the hard problems concurrently. PHMB, a broad-spectrum germicidal agent, has been used as a biocide in personal hygiene products, industrial disinfectants, and even cosmetics since 2005, 27 as it does not cause irritation to eyes or skin at normal-use concentrations, 28 nor induce hepatic injury when administered in drinking water and diet at certain concentrations. 29 The 3D porous DDM consists of collagen fibrils with polar side chains (above 90 wt% of the DDM) and highly anionic non collagen proteins (NCPs, below 10 wt% of the DDM).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms described above negatively affect the osmoregulation and metabolic activity of the cytoplasmic membrane and enzymes, leading to the disruption of the vital activity of the microbial cell, an osmotic ‘explosion’, and its death. This agent does not act on the lipid membranes of eukaryotic cells or human DNA [ 3 , 7 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the ability of PHMB to interact with polysaccharides are available and can be useful in the inactivation of biofilms. The extracellular matrix of biofilms contains polysaccharide molecules that provide spatial stability and protection from antiseptic agents that do not affect the organic components of the films [ 37 , 41 ]. If PHMB is able to accumulate in the intracanal biofilm matrix, this fact makes it the drug of choice in the treatment of chronic apical periodontitis.…”
Section: Discussionmentioning
confidence: 99%